2015
DOI: 10.1186/s12879-015-1233-0
|View full text |Cite
|
Sign up to set email alerts
|

Time series analysis of reported cases of hand, foot, and mouth disease from 2010 to 2013 in Wuhan, China

Abstract: BackgroundHand, foot, and mouth disease (HFMD) is an infectious disease caused by a group of enteroviruses, including Coxsackievirus A16 (CVA16) and Enterovirus A71 (EV-A71). In recent decades, Asian countries have experienced frequent and widespread HFMD outbreaks, with deaths predominantly among children. In several Asian countries, epidemics usually peak in the late spring/early summer, with a second small peak in late autumn/early winter. We investigated the possible underlying association between the seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 30 publications
5
35
0
Order By: Relevance
“…The increased HFMD in fall in Ningxia may be contributed to the climate conditions. As the temperature rises in spring, the risk of HFMD was increasing and reached the secondary peak, but as the temperature continued to rise, the HFMD risk dropped, similar to the threshold effect reported in Wuhan [33]. However, the exact conditions (range of temperature and humidity) that trigger this threshold effect are probably different as Wuhan is located in south China with humid climate.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The increased HFMD in fall in Ningxia may be contributed to the climate conditions. As the temperature rises in spring, the risk of HFMD was increasing and reached the secondary peak, but as the temperature continued to rise, the HFMD risk dropped, similar to the threshold effect reported in Wuhan [33]. However, the exact conditions (range of temperature and humidity) that trigger this threshold effect are probably different as Wuhan is located in south China with humid climate.…”
Section: Discussionsupporting
confidence: 58%
“…However, the positive relation does not hold universally, it is only valid for limited temperature range. For example, a study conducted in Wuhan, the capital city of Hubei province located in south China showed that temperature ranging from 20 to 25°C prevent HFMD infections in Wuhan [33]. Other climate conditions may also have a threshold effect.…”
Section: Discussionmentioning
confidence: 99%
“…EV71 was first isolated in California, USA [1]. Subsequently, EV71-associated hand-foot-mouse disease (HFMD) outbreaks occurred around the world [2][3][4][5][6][7]. Clinical manifestations of EV71 infection range from mild HFMD to severe encephalitis, pulmonary edema, and even death [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between meteorological factors and HFMD outbreaks is often nonlinear in nature. In 23 of the 61 studies reporting a positive association with temperature, cases occurred most frequently within a specific temperature range, and extreme heat was associated with fewer case outbreaks . Whether or not this relates to viral biology or changes in human behavior at the extremes of temperature is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Given its incubation period of 3–7 days, it may be transmitted via asymptomatic hosts. Moreover, affected persons may remain infectious after symptoms resolve; EV71 has been identified in infected persons’ feces several weeks after symptom onset and in throat swabs for up to 2 weeks after infection . Diagnoses of HFMD are generally clinical, but a throat swab or stool specimen may be sent to the laboratory for diagnosis by culture or PCR.…”
Section: Introductionmentioning
confidence: 99%